CONTRIBUTION À L’ÉTUDE DU MAGMATISME BASIQUE ASSOCIÉ AU VISÉEN SUPÉRIEUR DU BASSIN HERCYNIEN DE MECHRAA BEN ABBOU (REHAMNA-MAROC) - Kholaiq, Mariame; Saber, Najib; Zahour, Ghalem (European Scientific Journal, ESJ, 2015)
The synclinal of Gada Jennabia is located in Mechraa Ben Abbou basin (Rehamna-Morocco). An intense upper Visean basic magmatic activity recorded in the basin by sills of gabbros, dolerites and basalts. The lithological study, through four geological cross sections shows a diversification facies, represented by deterial, carbonate and pelagic sediments. Petrographical observations of these magmatic rocks indicate fairly constant mineralogical composition (plagioclase and strongly altered ferromagnesian minerals such as clinopyroxène). Observed textures are equigranular for the gabbros, intersertale ophitic and subophitic for the dolerite and microlithic porphyritic vacuolar for the basaltes. A pronounced hydrothermal alteration of some facies is attested by the presence of calcite, chlorite, séricite and iron oxides. These magmatic events were comparable in four outcrops. They are interbedded in the sedimentary and metamorphic series and are mineralogically the equivalent of magmatic rocks identified in central Morocco and the Jebilets massive.